The Underlying Determinants and Impacts of the Substance Abuse Crisis in Knox, Whitley, and Laurel Counties - Rhodes, Mikaela B (2019)
Substance use has become a growing problem on a national, statewide, and local level. While the commonwealth of Kentucky has astonishing rates of substance use and abuse, the areas of Knox, Whitley, and Laurel counties of Kentucky are observing similar results within county lines. There are many social determinants that could potentially lead an individual to substance use or abuse which can often be unique to an area as well as the adverse effects of substance abuse on a community. Interviews were conducted with individuals in professions that directly relate to the substance abuse crisis in Knox, Whitley, and Laurel counties. Participants identified depression, easy access to prescription drugs, poverty, and family values and morals as potential determinants that lead individuals to substance use or abuse in Knox, Whitley, and Laurel counties. Participants identified children and families of substance abusers as the individuals that suffer the most as a result of substance abuse. Participants also identified employment, the economy, officer safety, safety of the general public, and other aspects of the community as being directly affected by substance abuse. Findings from the study were consistent with current literature